2008
DOI: 10.1523/jneurosci.1486-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Segregated and Integrative Connectivity Patterns in the Human Basal Ganglia

Abstract: Detailed knowledge of the anatomy and connectivity pattern of cortico-basal ganglia circuits is essential to an understanding of abnormal cortical function and pathophysiology associated with a wide range of neurological and neuropsychiatric diseases. We aim to study the spatial extent and topography of human basal ganglia connectivity in vivo. Additionally, we explore at an anatomical level the hypothesis of coexistent segregated and integrative cortico-basal ganglia loops. We use probabilistic tractography o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

99
659
4
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 717 publications
(772 citation statements)
references
References 68 publications
(67 reference statements)
99
659
4
1
Order By: Relevance
“…During active downregulation of food desire, we also found enhanced hemodynamic responses in the head of the caudate nucleus, a sub-region with specific connections to the lateral PFC, 31 supporting the notion of a prefrontalstriatal circuitry that allows cognitive integration of alternatives to guide subsequent behavior. 32,33 The impact of individual differences on brain activity Given the quite heterogeneous abilities of individuals to control their calorie intake, individual differences in genoand phenotype are of special interest in the context of eating behavior.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…During active downregulation of food desire, we also found enhanced hemodynamic responses in the head of the caudate nucleus, a sub-region with specific connections to the lateral PFC, 31 supporting the notion of a prefrontalstriatal circuitry that allows cognitive integration of alternatives to guide subsequent behavior. 32,33 The impact of individual differences on brain activity Given the quite heterogeneous abilities of individuals to control their calorie intake, individual differences in genoand phenotype are of special interest in the context of eating behavior.…”
Section: Discussionsupporting
confidence: 78%
“…As mentioned above, it is assumed that neurons in DS are sensitive to the integration of a reward and goaldirected behavior. Our regression analysis suggests that individuals with higher CRE show higher activation not only in the DLPFC but also in the interconnected caudate nucleus, 31 both sub-serving cognitive control over eating behavior.…”
Section: Discussionmentioning
confidence: 76%
“…6), an apparent ventrorostral to dorsocaudal gradient of low to high t-values may be observed in the putamen. Previous studies have shown a rostrocaudal functional gradient of inputs in the neostriatum, where motor and premotor cortices mainly project to dorsal and caudal areas of the putamen (Draganski et al, 2008;Haber, 2003;Haber and Gdowski, 2004;Lehericy et al, 2004), suggesting that the putamen voxels with high t-values observed in the present study may be within the regions involved in motor control. However, further studies are needed to elucidate the relationship between choice RT performance and MD within specific neostriatal regions.…”
Section: Discussionsupporting
confidence: 56%
“…Supporting Information Figure S4a shows group average maps of the SSCs that were most strongly connected with the PCG, MFG, OFG, or inferior parietal lobule, based on the atlas by Desikan et al (2006). Consistent with previous studies (Barnes et al, 2010; Choi et al, 2012; Di Martino et al, 2008; Draganski et al, 2008; Garcia‐Garcia et al, 2018; Janssen et al, 2015; Jaspers et al, 2017; Jung et al, 2014), the middle part of the putamen was most strongly connected with the PCG, the caudate nucleus was most strongly connected with the MFG, and the caudate nucleus extending to ventral striatum was most strongly connected with the OFG.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies of striatal functional architecture have revealed a well‐organized relationship for cerebrocortical‐striatal connectivity (Barnes et al, 2010; Choi et al, 2012; Di Martino et al, 2008; Draganski et al, 2008; Garcia‐Garcia et al, 2018; Janssen et al, 2015; Jaspers et al, 2017; Jung et al, 2014). We confirmed, as a positive control, that the larger‐scale observations could be replicated using the present data set.…”
Section: Resultsmentioning
confidence: 98%